Flexible broadband wave-absorbing material and preparation method thereof

By using ion gel technology of functional polymer frames and imidazole-type ionic liquids in electromagnetic wave absorption materials, a micro-phase separation structure is formed, which solves the problems of large weight, poor flexibility and narrow frequency bands of traditional materials, and realizes electromagnetic waves of wide frequency bands Absorption and good mechanical properties, suitable for high-frequency applications such as wearable devices.

CN119505051APending Publication Date: 2025-02-25NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411563036.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional electromagnetic wave absorbing materials have problems such as large weight, poor flexibility, and narrow wave absorption frequency band, which are difficult to meet the high requirements of wearable electronic devices and military applications. At the same time, their preparation process is complex and costly.

Method used

Using a functional polymer framework and a liquid with strong electromagnetic wave absorption characteristics, the wideband electromagnetic wave absorption is achieved through the micro-phase separation structure of the ionic gel. The material consists of polymer monomers and imidazole-type ionic liquids. It forms a microscopic three-dimensional network structure through one-step polymerization, which has the characteristics of flexibility, controllability and low cost.

Benefits of technology

It realizes electromagnetic wave absorption in wide frequency bands, covering a wide frequency range from low frequency to high frequency, has good mechanical properties and environmental friendliness, and is suitable for wearable electronic devices and other high frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505051A_ABST
    Figure CN119505051A_ABST
Patent Text Reader

Abstract

The invention provides a flexible broadband wave-absorbing material and a preparation method thereof.The ionic gel flexible broadband wave-absorbing material is prepared through in-situ photopolymerization of imidazole type ionic liquid and polymer monomers, firstly, the polymer monomers are dissolved in the imidazole type ionic liquid, and a homogeneous solution is prepared; then adding a photoinitiator into the homogeneous solution to obtain an ionic gel precursor solution; and initiating a polymerization reaction through ultraviolet irradiation, and carrying out post-treatment on the obtained product to finally obtain the ionic gel flexible broadband wave-absorbing material. The preparation method is beneficial to large-scale production, the preparation process is simple, the raw materials are cheap and easy to obtain, and the prepared ionic gel wave-absorbing material has the advantages of flexibility, wide effective absorption frequency band, good mechanical property and environmental friendliness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of electromagnetic absorbing materials, and in particular relates to a flexible broadband absorbing material with a microphase separation structure. Background Art

[0002] Electromagnetic wave absorbing materials are mainly used in the military field, such as stealth technology, radar detection, etc. With the maturity of technology and the increase in application demand, their application fields have gradually expanded to the civilian field, such as anti-interference protection of electronic equipment, signal enhancement of wireless communication, etc. With the rapid development of electronic communication technology, the frequency of electromagnetic waves is getting higher and higher, and the signal transmission is getting farther and farther, resulting in increasingly serious electromagnetic interference and electromagnetic pollution problems, which not only affect human life and health, but also are not friendly to the environment and destroy the stability of the ecosystem. Traditional absorbing materials often have problems such as heavy weight, poor flexibility, and narrow absorbing frequency band, which limits their application scope. With the development of the times, the technological progress of wearable electronic devices and military applications has also put forward higher requirements for electromagnetic wave absorbing materials. In addition to the traditional requirements of lightness, thinness and width, they also need to have some other applications such as green environmental protection and processability. Therefore, it is particularly important to develop new absorbing materials to reduce the adverse effects of electromagnetic waves.

[0003] Gels are cross-linked polymer networks that can retain large amounts of liquid and maintain a 3D hierarchical structure. Gels and gel-derived materials have various unique features, including diverse compositions, desired ionic / electronic conductivity, high transparency, and structural flexibility to meet long-term performance and versatility in various applications. Today, the rapid development of soft robots, deformable structures, and camouflage has driven the demand for flexible and microwave-invisible materials in electronic countermeasures and precision equipment protection applications; microwave absorbing materials (MAMs), such as carbon-based materials (graphene, MXene, carbon nanotubes), metal-based materials (transition metal oxides / sulfides, alloys), and conductive polymers provide superb absorption efficiency, but very limited controllability and poor processing performance. Recently, researchers have developed some absorbers for more complex target applications, such as superstructures and polymer-reinforced composites. However, due to their fine control characteristics, limited durability, unsatisfactory stretchability, and relatively high cost, gel absorbers still need further exploration and research.

[0004] At present, there are few studies on gel-based electromagnetic wave absorbing materials. The patent CN116514129A applied by Northwestern Polytechnical University discloses "a method for preparing a super-hydrophobic composite gel absorbing material", which has the characteristics of super-hydrophobic layer and broadband electromagnetic wave absorption, but still needs to add other materials such as graphite, and the preparation process is complicated. Only some scientific research literature has explored gel absorbing materials, but there is still a problem of narrow bandwidth.

[0005] Ionic liquids (ILs), as a class of room-temperature molten salts, have tunable physicochemical properties (yin-yang pairs), negligible vapor pressure, and high ionic conductivity (0.1-81 mS / cm). Ionic gels, which form microphase-separated structures in situ in a one-step process by fixing ionic liquids in polymer networks, inherit these properties, which allows them to be used at temperatures far above ambient temperature. In addition, there are few studies on the electrical response mechanisms of gel-based materials. Ionic gel-based absorbers, due to their certain ionic conductivity, can facilitate good impedance matching and provide a novel platform for the development of efficient, customizable, and low-cost electromagnetic wave absorbers. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the present invention provides a flexible broadband absorbing material, which utilizes the joint contribution of a functional polymer framework and a liquid with strong electromagnetic wave absorption characteristics to overcome the shortcomings of defects and vacancies in current absorbers, and uses ion gels with controllable physical and chemical properties to overcome the shortcomings of uncontrollable performance of traditional absorbers, which is conducive to large-scale production, has a simple preparation process, and uses cheap and readily available raw materials. The prepared ion gel absorbing material has the advantages of flexibility, wide effective absorption bandwidth, good mechanical properties, and environmental friendliness.

[0007] The technical solution adopted by the present invention to solve the technical problem is: a flexible broadband absorbing material, the components of which include 20-50% by mass of a polymer monomer and 50-80% by mass of an imidazole type ionic liquid, the mass percentages of which add up to 100%.

[0008] The high molecular monomer is N-isopropylacrylamide, acrylic acid, acrylamide, methacrylic acid or methyl methacrylate.

[0009] The ionic liquid is 1-methylimidazole trichloropropyltriethoxysilane, 1-methylimidazole chloride, 1-butyl-3-methylimidazole chloride, 1-ethyl-3-methylimidazole acetate or 1-allyl-3-methylimidazole chloride.

[0010] The present invention also provides a method for preparing the flexible broadband absorbing material, comprising the following steps:

[0011] 1) Weigh a certain amount of polymer monomer and dissolve it in an imidazole-type ionic liquid at a mass ratio of 2:1 to 5:1 until the polymer monomer is completely dissolved to form a homogeneous solution;

[0012] 2) adding a photoinitiator to the homogeneous solution obtained in step 1) until the photoinitiator is completely dissolved to obtain an ion gel precursor solution;

[0013] 3) pouring the ion gel precursor liquid into the mold, initiating the polymerization reaction by ultraviolet light irradiation, and finally forming a framework structure with polymer molecular chains connected or entangled with each other, and the gaps in the framework are filled with ionic liquids of anions and cations as dispersion media. The microscopic level shows a microphase separation structure;

[0014] 4) Post-treating the product of step 3) to obtain the final ion gel flexible broadband absorbing material.

[0015] In the step 1), the polymer monomer is heated and ultrasonically or stirred until it is completely dissolved, the heating temperature is 30-80° C., the ultrasonic time is 10-50 min, and the stirring method is magnetic stirring, and the stirring time is 10-50 min.

[0016] In the step 2), ultrasonic or stirring is performed at 40° C. until the photoinitiator is completely dissolved.

[0017] The photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2'-ethoxyacetophenone or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0018] In the step 3), when initiating the polymerization reaction by ultraviolet light irradiation, the homogeneous solution and the ion gel precursor liquid are kept at 40° C. and irradiated with ultraviolet light for 5-15 minutes.

[0019] The post-treatment includes heating and drying; the drying is carried out by vacuum drying at a temperature of 25° C. for a time of 2 h to 48 h.

[0020] The beneficial effects of the present invention are:

[0021] The experimental operation steps of the material of the present invention are simple, and a one-step in-situ polymerization is used to produce a microscopic phase separation structure. The material has broadband wave absorbing performance and can cover a wide frequency range from low frequency to high frequency. For example, in the embodiment PNipam-IL2, within the test range of 2-40 GHz, at a thickness of 4.7 mm, the effective bandwidth of RL<-10 dB (90% electromagnetic wave loss) reaches 34.98 GHz, and has good mechanical tensile properties, with a maximum stress of 11.5 MPa.

[0022] The material polymer monomer and ionic liquid of the present invention have low cost, and the one-step in-situ polymerization preparation using ultraviolet light induction is simple in steps, has low equipment requirements, small environmental pollution, low production cost, and can improve industrial production efficiency.

[0023] The flexible ion gel absorbing material prepared by the present invention has significant advantages in the application of wearable electronic devices. With its unique physical and chemical properties, this material can be customized to produce absorbing materials with different properties by adjusting the formula and process parameters, providing an efficient and flexible electromagnetic wave absorption solution for wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a flow chart of the preparation of ion gel PNipam-LI2.

[0025] Figure 2 The microwave absorption performance of ion gel PNipam-LI2 prepared based on 1MI-Si ionic liquid and Nipam.

[0026] Figure 3 This is a physical picture of the ion gel prepared in Example 1 of the present invention and its TEM picture.

[0027] Figure 4 This is a diagram of the mechanical properties of the ion gel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The present invention includes but is not limited to the following embodiments.

[0029] The invention uses imidazole ionic liquid and polymer monomer in-situ photopolymerization to prepare ion gel flexible broadband wave absorbing material, the components include 20-50% polymer monomer and 50-80% imidazole ionic liquid by mass fraction, and the mass percentage of polymer monomer and imidazole ionic liquid add up to 100%.

[0030] In order to achieve the above object, the present invention comprises the following steps:

[0031] 1. Weigh a certain amount of polymer monomer and imidazole ionic liquid, dissolve them in the ionic liquid according to a mass ratio (2:1-5:1), heat and ultrasonicate or stir until the monomer is completely dissolved, and prepare a homogeneous solution in which the polymer monomer is completely dissolved in the ionic liquid;

[0032] 2. Add the photoinitiator to the homogeneous precursor solution obtained in step 1, and ultrasonicate or stir at 40°C until it is completely dissolved, until a uniform and completely transparent solution is obtained, i.e., the ion gel precursor solution;

[0033] 3. Pour the ion gel precursor liquid into a suitable mold and initiate the polymerization reaction by ultraviolet irradiation for 5-15 minutes. In order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor liquid are kept at 40°C during the photoinduced polymerization. Finally, a macroscopic three-dimensional network structure with a framework structure in which polymer molecular chains are interconnected or entangled and the gaps are filled with ionic liquids of anions and cations as dispersion media is formed, and the microscopic level shows a microphase separation structure.

[0034] 4. Post-processing is performed under specific conditions, such as heating, drying, etc., to enhance the mechanical properties and absorbing properties of the material, and obtain the final ion gel flexible broadband absorbing material.

[0035] As a further illustration of the present invention, the polymer monomer is N-isopropylacrylamide (Nipam), acrylic acid (AA), acrylamide (AAm), methacrylic acid (MAA) or methyl methacrylate (MMA).

[0036] As a further illustration of the present invention, the ionic liquid is 1-methylimidazolium trichloropropyltriethoxysilane (1MI-Si), 1-methylimidazolium chloride; 1-butyl-3-methylimidazolium chloride ([BMIM]Cl), 1-ethyl-3-methylimidazolium acetate ([EMIM]Ac) or 1-allyl-3-methylimidazolium chloride ([AMIM]Cl).

[0037] As a further illustration of the present invention, the heating temperature is 30-80°C.

[0038] As a further illustration of the present invention, the stirring method is magnetic stirring, and the stirring time is 10-50 min.

[0039] As a further illustration of the present invention, the ultrasonic time is 10-50 min.

[0040] As a further illustration of the present invention, the crosslinking agent includes polymethacrylate (MBA), N,N'-methylenebisacrylamide (MBAA), 1,4-BDDMA1,4-butanediol dimethacrylate, ethylene glycol dimethacrylate (EGDMA) or ethylene glycol diacrylate (EGDA).

[0041] As a further illustration of the present invention, the initiator includes 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (I2959), 2'-ethoxyacetophenone (DEAP) or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO).

[0042] As a further illustration of the present invention, the ultraviolet light region of the ultraviolet lamp is 250-420 nm.

[0043] As a further illustration of the present invention, the microstructure of the prepared ion gel includes a microphase separation structure, a phase separation structure or a bicontinuous microstructure.

[0044] As a further illustration of the present invention, in order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor solution were maintained at 40°C during the photoinduced polymerization.

[0045] As a further illustration of the present invention, the temperature of the vacuum drying oven is 25° C. and the time is 2 h-48 h.

[0046] Example 1

[0047] ① Weigh the polymer monomer Nipam (0.5 g) and the imidazole-type ionic liquid 1MI-S (0.25 g) and dissolve them in the ionic liquid at a mass ratio of 2:1, heat and ultrasonicate or stir until the monomer is completely dissolved, and prepare a homogeneous solution in which the polymer monomer is completely dissolved in the ionic liquid;

[0048] ② Add the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) (photoinitiator, 0.1 wt% relative to monomer) to the homogeneous precursor solution obtained in step 1, and ultrasonicate or stir at 40° C. until it is completely dissolved, until a uniform and completely transparent solution is obtained, i.e., an ion gel precursor solution;

[0049] ③ Pour the ion gel precursor liquid into a polytetrafluoroethylene mold. Use a 365nm ultraviolet lamp to irradiate for 10 minutes to initiate photopolymerization to obtain an ion gel. In order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor liquid were kept at 40°C during the photoinduced polymerization;

[0050] ④ After photopolymerization, the transparent block polymer PNipam-IL1 was obtained by cooling and standing for 12 hours. The final test results showed that the absorption performance was an effective bandwidth of 32.35 GHz at 4.7 mm, and a minimum reflection loss (RLmin) of -65.9 dB.

[0051] Example 2

[0052] ① Weigh the polymer monomer Nipam (0.5 g) and the imidazole type ionic liquid 1MI-S (0.5 g) and dissolve them in the ionic liquid in a mass ratio of 1:1, heat and ultrasonicate or stir until the monomer is completely dissolved, and prepare a homogeneous solution in which the polymer monomer is completely dissolved in the ionic liquid;

[0053] ② Add the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) (photoinitiator, 0.1 wt% relative to monomer) to the homogeneous precursor solution obtained in step 1, and ultrasonicate or stir at 40° C. until it is completely dissolved, until a uniform and completely transparent solution is obtained, i.e., an ion gel precursor solution;

[0054] ③ Pour the ion gel precursor liquid into a polytetrafluoroethylene mold. Use a 365nm ultraviolet lamp to irradiate for 10 minutes to initiate photopolymerization to obtain an ion gel. In order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor liquid were kept at 40°C during the photoinduced polymerization;

[0055] ④ After photopolymerization, the transparent block polymer PNipam-IL2 was obtained by cooling and standing for 12 hours. The final test results showed that the absorption performance was an effective bandwidth of 34.98 GHz at 4.7 mm and a minimum reflection loss (RLmin) of -57.58 dB.

[0056] Example 3

[0057] ① Weigh the polymer monomer Nipam (0.5 g) and the imidazole-type ionic liquid 1MI-S (1 g) and dissolve them in the ionic liquid in a mass ratio of 1:2, heat and ultrasonicate or stir until the monomer is completely dissolved, and prepare a homogeneous solution in which the polymer monomer is completely dissolved in the ionic liquid;

[0058] ② Add the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) (photoinitiator, 0.1 wt% relative to monomer) to the homogeneous precursor solution obtained in step 1, and ultrasonicate or stir at 40° C. until it is completely dissolved, until a uniform and completely transparent solution is obtained, i.e., an ion gel precursor solution;

[0059] ③ Pour the ion gel precursor liquid into a polytetrafluoroethylene mold. Use a 365nm ultraviolet lamp to irradiate for 10 minutes to initiate photopolymerization to obtain an ion gel. In order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor liquid were kept at 40°C during the photoinduced polymerization;

[0060] ④ After photopolymerization, the transparent block polymer PNipam-IL3 was obtained by cooling and standing for 12 hours. The final test results showed that the absorption performance was an effective bandwidth of 31.71 GHz at 4.7 mm and a minimum reflection loss (RLmin) of -59.83 dB.

[0061] Example 4

[0062] ① Weigh the polymer monomer Nipam (0.5 g) and the imidazole-type ionic liquid 1MI-S (1.5 g) and dissolve them in the ionic liquid at a mass ratio of 1:3, heat and ultrasonicate or stir until the monomer is completely dissolved, and prepare a homogeneous solution in which the polymer monomer is completely dissolved in the ionic liquid;

[0063] ② Add the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (TPO) (photoinitiator, 0.1 wt% relative to monomer) to the homogeneous precursor solution obtained in step 1, and ultrasonicate or stir at 40° C. until it is completely dissolved, until a uniform and completely transparent solution is obtained, i.e., an ion gel precursor solution;

[0064] ③ Pour the ion gel precursor liquid into a polytetrafluoroethylene mold. Use a 365nm ultraviolet lamp to irradiate for 10 minutes to initiate photopolymerization to obtain an ion gel. In order to prevent the crystallization of Nipam monomers during the preparation of the ion gel, the homogeneous solution and the ion gel precursor liquid were kept at 40°C during the photoinduced polymerization;

[0065] ④ After photopolymerization, the transparent block polymer PNipam-IL4 was obtained by cooling and standing for 12 hours. The final test results showed that the absorption performance was an effective bandwidth of 31.15 GHz at 4.7 mm and a minimum reflection loss (RLmin) of -58.49 dB.

[0066] Table 1 Comparison of indicators of various embodiments

[0067]

[0068] In summary, the ion gel absorbing material prepared in the present invention has the advantages of flexibility, wide effective absorption bandwidth, good mechanical properties, etc.

Claims

1. A flexible broadband absorbing material, characterized in that: The components include 20-50% of high molecular monomer and 50-80% of imidazole type ionic liquid in mass fraction, and the mass percentage of the high molecular monomer and the imidazole type ionic liquid is added up to 100%.

2. The flexible broadband absorbing material according to claim 1, characterized in that: The high molecular monomer is N-isopropylacrylamide, acrylic acid, acrylamide, methacrylic acid or methyl methacrylate.

3. The flexible broadband absorbing material according to claim 1, characterized in that: The ionic liquid is 1-methylimidazole trichloropropyltriethoxysilane, 1-methylimidazole chloride, 1-butyl-3-methylimidazole chloride, 1-ethyl-3-methylimidazole acetate or 1-allyl-3-methylimidazole chloride.

4. A method for preparing the flexible broadband absorbing material according to claim 1, characterized in that: The following steps are involved: 1) Weigh a certain amount of polymer monomer and dissolve it in an imidazole-type ionic liquid at a mass ratio of 2:1 to 5:1 until the polymer monomer is completely dissolved to form a homogeneous solution; 2) adding a photoinitiator to the homogeneous solution obtained in step 1) until the photoinitiator is completely dissolved to obtain an ion gel precursor solution; 3) pouring the ion gel precursor liquid into the mold, initiating the polymerization reaction by ultraviolet light irradiation, and finally forming a framework structure with polymer molecular chains connected or entangled with each other, and the gaps in the framework are filled with ionic liquids of anions and cations as dispersion media. The microscopic level shows a microphase separation structure; 4) Post-treating the product of step 3) to obtain the final ion gel flexible broadband absorbing material.

5. The method for preparing the flexible broadband absorbing material according to claim 4, characterized in that: In the step 1), the polymer monomer is heated and ultrasonically or stirred until it is completely dissolved, the heating temperature is 30-80° C., the ultrasonic time is 10-50 min, and the stirring method is magnetic stirring, and the stirring time is 10-50 min.

6. The method for preparing the flexible broadband absorbing material according to claim 4, characterized in that: In the step 2), ultrasonic or stirring is performed at 40° C. until the photoinitiator is completely dissolved.

7. The method for preparing a flexible broadband absorbing material according to claim 4, characterized in that: The photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2'-ethoxyacetophenone or 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

8. The method for preparing a flexible broadband absorbing material according to claim 4, characterized in that: In the step 3), when initiating the polymerization reaction by ultraviolet light irradiation, the homogeneous solution and the ion gel precursor liquid are kept at 40° C. and irradiated with ultraviolet light for 5-15 minutes.

9. The method for preparing a flexible broadband absorbing material according to claim 4, characterized in that: The post-treatment includes heating and drying; the drying is carried out by vacuum drying at a temperature of 25° C. for a time of 2 h to 48 h.

Citation Information

Patent Citations

  • Solid super acid-ionic liquid composite solid supported catalyst and preparation method thereof

    CN102698812A

  • Phase-change ionic gel, preparation method thereof and ionic device

    CN111995771A

  • Ionic liquid composite hydrogel wave-absorbing material as well as preparation method and application thereof

    CN117126428A

  • Imidazole type ionic liquid compounded MCNTs-based solvent-free nanofluid and preparation method thereof

    CN118359189A

  • Photocrosslinked hydrogels blended composition, preparation and use thereof

    US20230010001A1